The buddy system: A randomized controlled experiment of the benefits and costs of dieting in pairs. (December 2019) - Incollingo Rodriguez, Angela C; Rodriguez, Anthony; Callahan, Lauren C; Saxbe, Darby; Tomiyama, A Janet
A total of 67 pairs of female roommates were randomized into a diet condition: (1) both ate normally; (2) one dieted, the other ate normally; and (3) both dieted. Adherence, weight loss, anxiety, depression, disordered eating symptoms, and stress were measured. Dieters lost more weight than non-dieters, but average loss was <1 pound. Pairs where both dieted reported higher anxiety, depression, and disordered eating than one-dieter pairs. Structural equation models revealed an interrelated network of stress, anxiety, depression, and disordered eating. This was weakest when one roommate dieted. The "buddy system" may not promote weight loss, but living with a non-dieting partner may buffer consequences.